Wine production from ripen pond apple (Annona glabra L.) fruit - Minh, Nguyen Phuoc (Plant Science Today, 2022)
Pond apple (Annona glabra L.) trees were widely distributed in swamp regions of Mekong Delta, Vietnam. Pond apple fruits turned from green to yellow when ripening. Ripen pond apple fruits contained numerous phenolic constituents with valuable phytochemical benefits. However, ripen pond apple fruits were not successfully utilized as other commercial fruits. This research examined the possibility of wine production utilized from ripen pond apple fruits. Different various technical variables of fermentation affecting to the quality of pond apple wine were thoroughly examined. Ripen pond apple fruits were naturally collected from Soc Trang province, Vietnam. Ripen pond apple fruits were peeled, blended, deseeded, crushed, enzyme-treated (pectinase 25 mg/L), added with sugar (5-13% w/w), pasteurized (sulphite 30 mg/L), inoculated with yeast Saccharomyces pastorianus ratio (0.1-0.5%), macerated temperature (14-22oC) in different time (6-14 days). Malolactic fermentation was performed in anaerobic condition at 12oC in different durations (4-20 weeks). At the end of malolactic fermentation, wine was racked and clarified with different fining agents (bentonite, polyvinylpyrrolidone, wheat gluten, gelatin, kaolin) at 0.03% (v/v). Results showed that must should be added with 9% sugar and 0.4% yeast inoculation, fermentation temperature of 16oC in 10 days. Malolactic fermentation could be terminated at 12 weeks. Gelatin revealed the best candidate among different clarifying agents to remove turbidity in pond apple wine while retaining the most total phenolic content and antioxidant capacity. Under above technical variable conditions, fermentation gave the high ethanol content (4.26±0.02 % v/v); the total phenolic content (32.79±0.00 mg GAE/100 ml), 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging (11.84±0.01 %), overall acceptance (8.34±0.01 score) meanwhile low turbidity (24.41±0.00 NTU) was also noticed. High ethanol content and phytochemical retention contributed to the high sensory score of pond apple wine. These quality parameters were acceptable for an alcoholic drink. Ripen pond apple fruit would be a promising carbohydrate source to convert into a new fruit wine with a pleasant alcoholic flavor and attractive appearance.